1994
DOI: 10.1126/science.8160012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-6 in Mucosal IgA Antibody Responses in Vivo

Abstract: In mice with targeted disruption of the gene that encodes interleukin-6 (IL-6), greatly reduced numbers of immunoglobulin A (IgA)-producing cells were observed at mucosae and grossly deficient local antibody responses were recorded after mucosal challenge with either ovalbumin or vaccinia virus. The IgA response in the lungs was completely restored after intranasal infection with recombinant vaccinia viruses engineered to express IL-6. These findings demonstrate a critical role for IL-6 in vivo in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
221
3
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(241 citation statements)
references
References 39 publications
11
221
3
6
Order By: Relevance
“…Culturing B cells in vitro with anti-IL-6 antibodies inhibited immunoglobulin production even when added on the fourth day of an 8-day culture, indicating that IL-6 acts on the late phase of the B cell response (5). Interestingly, a marked reduction of mucosal IgA-producing cells has been observed, along with deficient local antibody responses in IL-6-deficient mice (40). In vivo data from an open-label study of tocilizumab in SLE indicate a reduction in anti-DNA antibody and serum IgG levels (37).…”
Section: Discussionmentioning
confidence: 99%
“…Culturing B cells in vitro with anti-IL-6 antibodies inhibited immunoglobulin production even when added on the fourth day of an 8-day culture, indicating that IL-6 acts on the late phase of the B cell response (5). Interestingly, a marked reduction of mucosal IgA-producing cells has been observed, along with deficient local antibody responses in IL-6-deficient mice (40). In vivo data from an open-label study of tocilizumab in SLE indicate a reduction in anti-DNA antibody and serum IgG levels (37).…”
Section: Discussionmentioning
confidence: 99%
“…It functions in the terminal differentiation of B cells into plasma cells, the proliferation of lymphocytes and the regulation of IL-2 receptor expression [22][23][24]34] . Furthermore, IL-6 plays a critical role in the development of local IgA antibody responses and vector-directed cytokine gene therapy in vivo [29] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of IL-6 as a vaccine adjuvant can significantly elicit both the mucosal and systemic immune responses, which provides a method of stimulating mucosal immunity with the combined DNA plasmid and il-6 gene [20,28] . In vivo studies have shown that IL-6 plays a critical role in the development of mucosal IgA antibody responses, which acts as the first line of the host immune defense and is critical for the protection of mucosal tissues [29] . In this study, we determined whether co-immunization of the il-6 gene with pCIA-P induced higher levels of IgA in the saliva and IgG in the serum against PAc in intranasally immunized mice and provided better protection against dental caries in rats.…”
Section: Introductionmentioning
confidence: 99%
“…While IL-6 appears to have little to do with the day-to-day "housekeeping" functions of the body, along with other cytokines it represents an important frontline component of the body's armory against infection or tissue damage (Akira et al, 1993;Nicola, 1994). In vivo studies using IL-6 knockout mice demonstrate that, while IL-6-deficient mice develop normally, they have impaired immune and acute-phase responses (Fattori et al, 1994;Kopf et al, 1994;Poli et al, 1994;Ramsay et al, 1994).…”
mentioning
confidence: 99%